Moisture Mode Oscillations in Steady‐State Weak Temperature Gradient Simulations - Miguel Bernardez; Larissa Back (Journal of Advances in Modeling Earth Systems)
Abstract Weak Temperature Gradient modeling using a small cloud‐resolving model admits multiple equilibria depending upon the initial model conditions. There were thought to be two equilibrium states, a moist precipitating state and a dry non‐precipitating state. In this paper, we describe a periodic equilibrium which has oscillatory behavior from static boundary conditions. We show that the periodic oscillation has the characteristics of a moisture mode in the vertical dimension, instead of in the horizontal dimension. Further, we show that the oscillation occurs due to a balance between vertical advection and radiation, which can be described using a simple two vertical mode model. The first mode is related to the column relative humidity anomaly and a first baroclinic mode, while the second mode is related to a moisture dipole centered around 600 hPa and a second baroclinic mode. The first mode is associated with the generation of a moisture dipole, while the second mode is associated with the generation of a column moisture anomaly.